2007
DOI: 10.2514/1.24636
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cathode Configuration on Hall Thruster Cluster Plume Properties

Abstract: Clusters of Hall thrusters are being considered for use on a variety of missions requiring electric propulsion systems capable of operating at power levels in excess of the current state of the art. One of the key factors to be considered in determining the optimum cluster architecture is the configuration of the electron-emitting cathode(s). This work presents experimentally determined plume properties and discharge current characteristics obtained with multiple thrusters coupled to a single cathode. Spatiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…A quasineutral boundary condition is used, where electrons are injected from the boundary so that the electron density becomes equal to the ion density at the adjacent cell center. The injected electrons are assumed to be a Maxwellian distribution with an electron temperature of 3 eV [55,56]. Considering that the ion and electron densities are on the cell center and the electric fields are on the cell interface, Gauss's law in 1D results in…”
Section: Boundary Conditionmentioning
confidence: 99%
“…A quasineutral boundary condition is used, where electrons are injected from the boundary so that the electron density becomes equal to the ion density at the adjacent cell center. The injected electrons are assumed to be a Maxwellian distribution with an electron temperature of 3 eV [55,56]. Considering that the ion and electron densities are on the cell center and the electric fields are on the cell interface, Gauss's law in 1D results in…”
Section: Boundary Conditionmentioning
confidence: 99%
“…The development of the head is also an important factor in the design of a Hall thruster cluster system, however, it is critical to investigate and evaluate the unique perspective to the cluster system, which is the interference between the plumes from each head. Research on several cluster systems have been ongoing so far (Beal et al, 2005;Lobbia et al, 2007;Walker et al, 2007;Zakharenkov et al, 2005;Tverdokhlebov et al, 2005). Beal et al showed that the plume property was influence in multihead operation (Beal et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Research on several cluster systems have been ongoing so far (Beal et al, 2005;Lobbia et al, 2007;Walker et al, 2007;Zakharenkov et al, 2005;Tverdokhlebov et al, 2005). Beal et al showed that the plume property was influence in multihead operation (Beal et al, 2005). Lobbia et al showed thrust boost due to clustering (Lobbia et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Hofer, et al 4 and Jameson, et al, 8 noticed significant performance improvements by placing the cathode in the center of the HET rather than outside, and Beal, Gallimore and Hargus have inferred from probe measurements that cathode placement and number in a cluster of HETs will affect performance. 6 To the best of our knowledge there are two studies available in the literature that specifically address the effect of cathode position on thruster performance across a range of cathode locations. In the first, by Tilley, et al the authors note an increase in cathode coupling voltage as the cathode is moved forward of the exit plane.…”
Section: Introductionmentioning
confidence: 99%